2019
DOI: 10.1111/nep.13491
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune‐inflammation index could estimate the cross‐sectional high activity and the poor outcomes in immunosuppressive drug‐naïve patients with antineutrophil cytoplasmic antibody‐associated vasculitis

Abstract: SII at diagnosis could estimate the cross-section severe AAV and predict the poor outcomes in AAV patients. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 25 publications
0
36
2
2
Order By: Relevance
“…In a study of Guo et al, the optimal cutoff values for the prediction of survival were 419.6 for the SII in lung cancer patients [ 33 ]. Kim et al, calculated the optimal cut-off of SII at diagnosis using AUROC (area 0.696, 95% confidence interval (CI) 0.612, 0.781), and found that 1,573.56 of SII was a strongest value for poor outcome [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Guo et al, the optimal cutoff values for the prediction of survival were 419.6 for the SII in lung cancer patients [ 33 ]. Kim et al, calculated the optimal cut-off of SII at diagnosis using AUROC (area 0.696, 95% confidence interval (CI) 0.612, 0.781), and found that 1,573.56 of SII was a strongest value for poor outcome [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…SII, which is positively correlated with neutrophil, platelet counts and inversely correlated with lymphocyte count, was first developed by Hu et al in 2014 [ 11 ]. Later, several studies also evaluated its prognostic values in various tumors, such as renal cell cancer, lung cancer, prostate cancer and in vasculitis [ 12 14 ]. Thus, the aim of our study was to evaluate the role of SII at admission in predicting in-hospital mortality and characterize the factors that trigger unfavorable outcomes in IE.…”
Section: Introductionmentioning
confidence: 99%
“…Other predictive factors included the presence of CRP and ANC. Derived indexes, such as NLR [36,37] and SII [38] have previously been used as prognostic markers for other inflammatory and autoimmune conditions, as well as in the context of malignant disease, and were also associated with an increased risk of relapse. In our study population, ulceration at presentation was the strongest predictor of recurrence (OR 18.6), and elevated pre‐treatment values of ESR, CPR, ANC, NLR and SII were also associated with a poor prognosis in terms of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Weitere prädiktive Faktoren waren CRP und ANC. Abgeleitete Indizes wie NLR [36,37] und SII [38] wurden früher als prognostische Marker für andere Entzündungs‐ und Autoimmunkrankheiten sowie im Zusammenhang mit malignen Erkrankungen verwendet und waren ebenfalls mit einem erhöhten Rückfallrisiko verbunden. In unserer Studienpopulation waren Ulzerationen bei der Vorstellung der stärkste Prädiktor für ein Rezidiv (OR 18,6), und erhöhte Werte von ESR, CPR, ANC, NLR und SII vor der Behandlung waren ebenfalls mit einer schlechten Prognose hinsichtlich eines Rezidivs verbunden.…”
Section: Diskussionunclassified